Analisis Yuridis Tindak Pidana Mempergunakan Kesempatan Main Judi dalam KUHP - Sangaji, Rizky (Proceedings Series on Social Sciences & Humanities, 2024)
This juridical analysis of the criminal act of using the opportunity to gamble in the Criminal Code (KUHP) discusses the legal regulation of the criminal act of gambling via online platforms. In the digital era, the practice of online gambling has become a significant phenomenon. However, law enforcement against online gambling crimes still faces various obstacles and weaknesses. Therefore, this analysis focuses on applicable legal regulations, such as Article 303 of the Criminal Code, as well as Law no. 11 of 2008 concerning Information and Electronic Transactions (UU ITE), to find out how criminal acts of online gambling can be punished and overcome. This analysis also discusses the criminal sanctions that can be imposed, including imprisonment and fines, as well as effective prevention and law enforcement efforts.